5 Improving the diagnostic accuracy of apical hypertrophic cardiomyopathy. (6th June 2022) - Hughes, Rebecca; Shiwani, Hunain; Rosmini, Stefania; Augusto, Joao; Burke, Liam; Pierce, Iain; Castelletti, Silvia; Xue, Hui; Kellman, Peter; Lopes, Luis; Treibel, Thomas; Manisty, Charlotte; et al.
Abstract : Introduction: The diagnosis of apical hypertrophic cardiomyopathy (ApHCM) is contingent on demonstrating apical maximum wall thickness (MWT) of ≥15 mm; the same threshold as other HCM subtypes. However, the myocardium naturally tapers towards the apex in healthy individuals, so ≥15 mm MWT is proportionately higher in the apex than in naturally thicker basal segments. Using cardiac magnetic resonance (CMR), relative ApHCM has been described (typical ECG features, loss of apical tapering, cavity obliteration but hypertrophy<15 mm). Wall thickness measurement using machine learning now exceeds human performance. We aimed to redefine the optimal diagnostic threshold for ApHCM using segment-specific criteria based on a large cohort of healthy control subjects. Methods: Segmental wall thickness was measured using healthy subjects from the UK Biobank using a clinically validated machine learning algorithm. A normative reference range was established for all 16 segments, conditioned to body surface area (BSA), sex and age. Derived segment-specific wall thickness thresholds were used to define optimal disease thresholds for patients clinically managed with overt (MWT ≥15 mm) and relative ApHCM (MWT<15 mm, but typical ECG and imaging findings). Results: 4118 UK biobank subjects were used to define normal segmental thicknesses and reference ranges. These were applied to ApHCM (73 overt, 31 relative). There were no apical wall thickness age related differences. The upper limit of the 95% confidence interval corresponded to a combined maximum apical MWT for both males and females of 10.4 mm using non-indexed measurement, or 5.6 mm/m2 when indexed to BSA. Non-indexed segmental threshold identified 100% of ApHCM patients (true positives), 81% (25 of 31) relative ApHCM and 3% (115 of 4118) of healthy UK biobank subjects (false positives). Indexed segmental thresholds improved the diagnostic potential in relative ApHCM without an increase in false positives (100% of ApHCM patients, 84% (26 of 31) of relative ApHCM patients, and 3% healthy UK biobank (127 of 4118). Conclusion: We propose new diagnostic criteria for ApHCM using segmental indexed apical wall thickness of >5.6 mm/m2 to better identify inappropriate apical hypertrophy in those whose wall thickness does not meet current criteria for diagnosis. Conflict of Interest: nil